234k views
0 votes

f(x) = √(x)
Lim h=0
f(x+h) -f(x)/h​

User Saus
by
5.2k points

1 Answer

3 votes

Answer:
(1)/(2\sqrt x)

Explanation:


\lim_(h \to 0) f(x)=(f(x+h)-f(x))/(h)

f(x) =
\sqrt x\\

f(x+h) =
√(x+h)


\lim_(h \to 0) f(x)=(√(x+h)-\sqrt x)/(h)


=(√(x+h)-\sqrt x)/(h)\bigg((√(x+h)+\sqrt x)/(√(x+h)+\sqrt x)\bigg)


=((x + h)-(x))/(h(√(x+h)+\sqrt x))


=(h)/(h(√(x+h)+\sqrt x))


=(1)/(√(x+h)+\sqrt x)


=(1)/(√(x+0)+\sqrt x)


=(1)/(2\sqrt x)

User Illidanek
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.